Patency for autologous vein is superior to cadaveric vein in portal-mesenteric venous reconstruction. Issue 8 (August 2022) - Sutton, Thomas L.; Sandoval, Victor; Warner, David; Moneta, Gregory; Gilbert, Erin; Mayo, Skye C.; Politano, Amani D.; Maynard, Erin; Sheppard, Brett C.; Enestvedt, C. Kristian
Abstract: Background: Portal venous reconstruction (PVR) is often needed during resection of hepatopancreato-biliary (HPB) malignancies. Primary repair (PR), autologous vein (AV), or cryopreserved cadaveric vein (CCV) are frequently utilized, however relative patency is not well studied. Methods: All patients undergoing PVR between 2007-2019 at our center were identified. 3-year primary patency (PP), overall survival (OS), and survival-adjusted patency (SAP) were evaluated with Kaplan-Meier and Cox proportional hazards modeling. Results: One-hundred-twenty patients were identified with a median follow-up of 11 months. PR, AV, and CCV reconstruction were used in 28 (23%), 35 (29%), and 57 (48%) patients, respectively, with two (7%), four (11%), and 29 (51%) thromboses, respectively. 3-year PP was greater for both primary repair (90%) and AV (83%) compared to CCV (33%, both p<0.001). On multivariable analysis, CCV had worse 3-year PP (HR 7.89, p=0.005) and SAP (HR 2.09, p=0.02) compared to PR; AV reconstruction had equivalent oncologic and patency-related outcomes to PR (p>0.4 for both comparisons). Conclusions: Primary patency for PR and AV reconstruction is superior to CCV for PVR during resection of HPB malignancies. AV conduit should be the preferred choice of reconstruction when PR is not achievable. Surgeons should only use CCV when factors preclude PR/AV reconstruction.